Overexpression of T3SS translocation signals in Salmonella causes delayed attenuation - Abele, Taylor J; Billman, Zachary P; Harvest, Carissa K; Bryan, Alexia K; Larson, Heather N; Coers, Jörn; Miao, Edward A (Infection and immunity, 2024)
Engineering pathogens is a useful method for discovering new details of microbial pathogenesis and host defense. However, engineering can result in off-target effects. We previously engineered serovar Typhimurium to overexpress the secretion signal of the type 3 secretion system effector SspH1 fused with domains of other proteins as cargo. Such engineering had no virulence cost to the bacteria for the first 48 hours post infection in mice. Here, we show that after 48 hours, the engineered bacteria manifest an attenuation that correlates with the quantity of the SspH1 translocation signal expressed. In IFN-γ-deficient mice, this attenuation was weakened. Conversely, the attenuation was accelerated in the context of a pre-existing infection. We speculate that inflammatory signals change aspects of the target cell's physiology, which makes host cells less permissive to . Typhimurium infection. This increased degree of difficulty requires the bacteria to utilize its T3SS at peak efficiency, which can be disrupted by engineered effectors.